View of Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Photo showing an aerial view of the buildings, harbour and vegetation in Port of Spain, Trinidad.
Colour: Blue, Red and Green Hues ; Style: Landscape ; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Port of Spain; Buildings, Port of Spain; Harbors